Isocrates Free from Plato’s Shadow - Ribas, Marie-Noëlle (Araucaria, 2020)
Isocrates is commonly remembered as a logographer or as a distinguished professor of oratory, but never as a philosopher, although he persists in styling himself as such. No doubt this is largely due to Plato’s criticism, which has significant influence on the way Isocrates is still considered. According to Plato, Isocrates who promotes a kind of philosophy with no regard to truth but only to opinion, does not deserve to be seen as an accomplished philosopher. Despite his claims, Isocrates would fail to set himself apart from other sophists, with whom he does not wish to be confused. In this article, I want to free Isocrates from Plato’s disparaging view by showing what kind of philosophy Isocrates claimed to teach.